On the approach to the justification of a set of measures to protect the population in the area of chemical contamination - Kochelaev A.A. (Научно-технический вестник Брянского государственного университета)
The article presents an approach to the justification of a set of measures to protect the population in the area of chemical contamination. This approach is based on the assessment of the values of the indicator of protection of the population from the action of chemically hazardous substances.